Political News Preferences on Social Media Among Millennials and Gen Z in Bandung City in the 2024 Election Year - Ati Suprihatin; Dedy Suhaeri; Ferry Darmawan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2024)
The political year 2024 in Indonesia presents unique dynamics in political news consumption, especially among the Millennial and Gen Z generations. This study explores their preferences, habits, and patterns of political news consumption behavior and the factors influencing them, focusing on the city of Bandung as a case study. This study uses a descriptive analysis method with a qualitative approach through in-depth interviews with purposively selected informants to gain in-depth insights. The study results show that the intensity of Exposure to political news through social media plays a significant role in increasing Millennial and Gen Z interest in political issues. Instagram and TikTok are the leading platforms used because of their interactive features and short video content that is considered interesting, informative, and entertaining. In contrast, traditional media such as television and print are increasingly rarely used because they are considered less flexible and difficult to access. The preference for short video formats reflects the fast and dynamic lifestyle of the younger generation. In addition, their active involvement in political discussions on social media shows the great potential of this generation as a driver of change in the Indonesian political landscape. By utilizing social media platforms and relevant visual content, political stakeholders can increase the younger generation's involvement in the democratic process while strengthening their role in shaping the future of Indonesian politics.